The influence of orienting layers on blue phase liquid crystals in rectangular geometries - Sala-Tefelska, Marzena Maria; Orzechowski, Kamil; Sala, Filip A.; Woliński, Tomasz R.; Strzeżysz, Olga; Kula, Przemysław (Photonics Letters of Poland, 2018)
In this paper, the influence of homeotropic and homogeneous orienting layers is presented in a cell filled with chiral nematic liquid crystals stabilized in a blue phase. The change of selective Bragg reflection from red to blue light was observed for homogeneous layers in rectangular geometries. The growth of blue phase crystals domains in a glass cell as well an influence of temperature and the electric field on such a structure, are also presented. Full Text: PDF References F. Reinitzer, Beitrage zur Kenntniss des Cholestherins, Monatsh Chem. 9, 421-441, (1888). CrossRef J. Yan, M. Jiao, L. Rao, and S.-T. Wu, "Direct measurement of electric-field-induced birefringence in a polymer-stabilized blue-phase liquid crystal composite", Opt. Express 18, 11450-11455 (2010) CrossRef Y. Chen, D. Xu, S.-T. Wu, S.-i. Yamamoto, Y. Haseba, "A low voltage and submillisecond-response polymer-stabilized blue phase liquid crystal", Appl. Phys. Lett. 102, 141116 (2013) CrossRef Y. Huang, H. Chen, G. Tan, H. Tobata, S. Yamamoto, E. Okabe, Y.-F. Lan, C.-Y. Tsai, and S.-T. Wu, "Optimized blue-phase liquid crystal for field-sequential-color displays", Opt. Mater. Express 7, 641-650 (2017) CrossRef V. Sridurai, M. Mathews, C. V. Yelamaggad, G. G. Nair, "Electrically Tunable Soft Photonic Gel Formed by Blue Phase Liquid Crystal for Switchable Color-Reflecting Mirror", ACS Appl. Mater. Interfaces, 9 (45), 39569-39575 (2017) CrossRef E. Oton, E. Netter, T. Nakano, Y. D.-Katayama, F. Inoue, "Monodomain Blue Phase Liquid Crystal Layers for Phase Modulation", Sci. Rep. vol.7, 44575 (2017) CrossRef Q. Liu, D. Luo, X. Zhang, S. Li, Z. Tian, "Refractive index and absorption coefficient of blue phase liquid crystal in terahertz band", Liq. Cryst., Vol. 44, No. 2, pp. 348-354 (2017) CrossRef Y. Li, Y. Liu, Q. Li, S.-T. Wu, "Polarization independent blue-phase liquid crystal cylindrical lens with a resistive film", Appl. Opt., Vol. 51, No. 14, pp. 2568-2572 (2012) CrossRef M. M. Sala-Tefelska, K. Orzechowski M. Sierakowski, A. Siarkowska, T.R. Woliński, O. Strzeżysz, P. Kula, "Influence of cylindrical geometry and alignment layers on the growth process and selective reflection of blue phase domains", Opt. Mater. 75, 211-215, (2018) CrossRef H. Claus, O. Willekens, O. Chojnowska, R. Dąbrowski, J. Beeckman, K. Neyts, "Inducing monodomain blue phase liquid crystals by long-lasting voltage application during temperature variation", Liq. Cryst. 43 (5), 688-693, (2016) CrossRef M. Takahashi, T. Ohkawa, H. Yoshida, J. Fukuda, H. Kikuchi, M. Ozaki, "Orientation of liquid crystalline blue phases on unidirectionally orienting surfaces", J. Phys. D: Appl. Phys. 51 (10), 104003 (2018) CrossRef P. Joshi, X. Shang, J. De Smet, E. Islamai, D. Cuypers, G. Van Steenberge, S. Van Vlierberghe, P. Dubruel, H. De Smet, "On the effect of alignment layers on blue phase liquid crystals", Appl. Phys. Lett. 106, 101105 (2015) CrossRef K. Orzechowski, M.W. Sierakowski, M. Sala-Tefelska, P. Joshi, T.R. Woliński, H.D. Smet, "Polarization properties of cubic blue phases of a cholesteric liquid crystal", Opt. Mater. 69, 259-264 (2017) CrossRef P.-J. Chen, M. Chen, S.-Y. Ni, H.-S. Chen, Y.-H. Lin, "Influence of alignment layers on crystal growth of polymer-stabilized blue phase liquid crystals", pt. Mater. Express 6, 1003-1010 (2016) CrossRef CrossRef